The impact of trust in the news media on online news consumption and participation - Fletcher, R; Park, S (Taylor and Francis, 2017)
Trust has long been considered an important factor that influences people’s relationship with news. However, the increase in the volume of information available online, together with the emergence of new tools and services that act as intermediaries and enable interactivity around the news, may have changed this relationship. Using Reuters Institute Digital News Report survey data (N = 21,524), this study explores the impact of individual trust in the news media on source preferences and online news participation behaviour, in particular sharing and commenting, across 11 countries. The results show that those with low levels of trust tend to prefer non-mainstream news sources like social media, blogs, and digital-born providers, and are more likely to engage in various forms of online news participation. These associations tend to be strongest in northern European countries, but are weaker elsewhere. Seeking alternative views and attempting to validate the credibility of news may be among the motivations behind these associations.